Customer Perception towards Shopping Malls in Chennai - Girija, K; Ravi, G (International Journal of Computer Sciences and Engineering, 2025)
Consumer becomes a customer by a frequency of visits to shopping malls. The main objectives of the study are to identify and examine the perception of customer. Customer perception towards shopping malls in Chennai city is analyzed by the various factors such as ambience of the mall/shop, mall change the life style of consumers, mall enhances the consumer’s belief of want satisfaction, the physical facilities are visually appealing, perception way of shopping, identifying merchandise and convenience